Bauran Pemasaran Susu Bubuk Kedelai Merek Emyta pada UD Emyta di Kota Denpasar Provinsi Bali - TAMBUNSARIBU, JHON RONALD SAPUTRA; AMBARAWATI, I GUSTI AGUNG AYU; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
The Marketing M ix of Soybean Milk Podwer of Emyta Brand at UD Emyta Denpasar-Bali One of the soybean processed products in the form of drinks that is most easily digested by the body is soy milk.UD Emyta is one of the companies that produces powdered soy milk in the city of Denpasar. This study aims to determine the marketing mix of soybean milk powder carried out by UD Emyta  in terms of product concept, price, place/distribution and promotion and to find out the obstacles faced by the company in marketing Emyta’s soybean milk powder products. Based on the results of the research, soybean powder milk products are processed from the best imported raw soybeans. Marketing mix carried out by UD Emyta for products is that companies provide three types of packaging for different weight in marketing their products to make them look more attractive to consumers. For the type of packaging 150 grams and 250 grams, it is packed with aluminum foil packaged in a box and for a 500 gram type of packaging using plastic packaging. Pricing used by UD Emyta is a cost plus pricing method, which is to set prices based on costs added with percentage of costs. The price for small packages containing 150 grams was Rp 16,000, 250 grams was Rp 22,000 and 500 grams was Rp 34,000 respectively. The company uses retailers as intermediaries in the distribution of products so thattheproduct reaches the final consumer.Promotional activities used by companies are by using social media and giving discounts to each of their customers. Internal constraints faced are company performance in terms of promotions that are less effective. External constraints are the difficulty of finding quality raw materials and the presence of competitors of similar products which result in companies having to compete quite tightly.